2018
DOI: 10.1177/0309132518819503
|View full text |Cite
|
Sign up to set email alerts
|

Financial geography II: Financial geographies of housing and real estate

Abstract: Geographers have started studying residential (housing) and commercial real estate (offices, retail, leisure) at the intersection of financial and urban geographies to understand how the built environment – chunky and spatially fixed – has been turned into a (quasi-)financial asset – ‘unitized’ and liquid – through a range of regulatory and socio-technical changes and constructions. The financialization of real estate is not limited to the rise in household debt, mortgage securitization and international inves… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
86
0
4

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 143 publications
(90 citation statements)
references
References 133 publications
(138 reference statements)
0
86
0
4
Order By: Relevance
“…Likewise, mergers and acquisitions within the lenders of real estate finance—the banking sector—have helped sustain “abnormal sectoral profitability” for these firms and their shareholders in the era of financialisation (Christophers :864). Intense scrutiny by capital markets means real estate is expected to “perform according to a common standard of shareholder value‐creation” (Rutland :1175), resulting in what Aalbers (:379) notes are projects which “increasingly developed with an investor rather than a user in mind”. As property markets in general and income‐generating buildings in particular are sites to realise shareholder value for a variety of firms, investors demonstrate a willingness “for whatever reason hold a claim on rent rather than on some other form of future revenue” (Harvey :348).…”
Section: Rent Beyond the Rent Gap In The Era Of Shareholder Valuementioning
confidence: 99%
“…Likewise, mergers and acquisitions within the lenders of real estate finance—the banking sector—have helped sustain “abnormal sectoral profitability” for these firms and their shareholders in the era of financialisation (Christophers :864). Intense scrutiny by capital markets means real estate is expected to “perform according to a common standard of shareholder value‐creation” (Rutland :1175), resulting in what Aalbers (:379) notes are projects which “increasingly developed with an investor rather than a user in mind”. As property markets in general and income‐generating buildings in particular are sites to realise shareholder value for a variety of firms, investors demonstrate a willingness “for whatever reason hold a claim on rent rather than on some other form of future revenue” (Harvey :348).…”
Section: Rent Beyond the Rent Gap In The Era Of Shareholder Valuementioning
confidence: 99%
“…The top ten citing articles are published in 2019. The highest citation coverage of 25% is published by Aalbers (2019). The author indicated that financialization of real estate is not limited to the rise in household debt, or mortgage securitization and international investment in office markets, but also increasingly affects rental housing: private equity.…”
Section: Cluster #5-financial Geographiesmentioning
confidence: 99%
“…As an inherently spatial phenomenon (French, Leyshon, & Wainwright, 2011), the financialization process can manifest itself differently in different geographical contexts. As part of a growing research interest in finance, a significant body of work has developed within economic geography that examines the ways in which space and place shape financial decisions, allocations of capital, regulatory frameworks of global financial markets, the development of onshore and offshore financial centres, and financial landscapes more generally (e.g., Aalbers, 2018Aalbers, , 2019Coe, Lai, & Wójcik, 2014;Lai, 2017;Martin & Pollard, 2017). The literature also suggests that, rather than being a neutral lubricant in the economic system, finance shapes development trajectories of regions and localities.…”
Section: Introductionmentioning
confidence: 99%